Interpreting granulite facies events through rare earth element partitioning arrays - Taylor, Richard; Clark, Christopher; Harley, S.; Kylander-Clark, A.; Hacker, B.; Kinny, Peter (Wiley - Blackwell, 2017)
The use of rare earth element (REE) partition coefficients is an increasingly common tool in metamorphic studies, linking the growth or modification of accessory mineral geochronometers to the bulk silicate mineral assemblage. The most commonly used mineral pair for the study of high-grade metamorphic rocks is zircon and garnet. The link from U–Pb ages provided by zircon to the P–T information recorded by garnet can be interpreted in relation to experimental data. The simplistic approach of taking the average REE abundances for zircon and garnet and comparing them directly to experimentally derived partition coefficients is imperfect, in that it cannot represent the complexity of a natural rock system. This study describes a method that uses all the zircon analyses from a sample, and compares them to different garnet compositions in the same rock. Using the most important REE values, it is possible to define zircon–garnet equilibrium using an array rather than an average. The array plot describes partitioning between zircon and garnet using DYb and DYb/DGd as the defining features of the relationship. This approach provides far more sensitivity to mineral reactions and diffusional processes, enabling a more detailed interpretation of metamorphic history of the sample.